PEMANFAATAN LEMAK AYAM POTONG SEBAGAI BIODIESEL DENGAN KATALISATOR KALIUM HIDROKSIDA - , CHEFI ARDIANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aimed to process broiler fat into biodiesel using potasium hydroxide (KOH) catalyst and methanol. The fat was melted 50-80 Â°C then reacted by transesterification method with above solutions. The reaction produced fatty acid methyl ester (FAME) and glycerol. FAME was washed with aquadest then dried before analysis for biodiesel quality. The results show that not all of the samples meet the biodiesel standards of the United States, Europe Union. Australia, and Indonesia